2014
DOI: 10.1364/ol.39.004404
|View full text |Cite
|
Sign up to set email alerts
|

Core-pumped femtosecond Nd:fiber laser at 910 and 935  nm

Abstract: We report a core-pumped all-normal dispersion mode-locked Nd-doped fiber laser at 910 and 935 nm. The pulse is compressed to 198 fs, and the pulse energy is 1.3 nJ. The slope efficiency is more than 14%. This laser is tested as the optical source for the two-photon fluorescence imaging of pollen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Its core numerical aperture (NA, ~0.14) has been designed to match with the standard single-mode fiber (SMF), e.g., the Nufern 1060-xp and Corning HI 1060. Typically, NDF exhibits a strong emission at around 1060 nm, and thus the NDF cavity easily oscillates at 1060 nm rather than 900 nm [16,17]. The NDF used here has a W-type refractive index profile, and more detailed information can be found iXblue.…”
Section: The Swept Source At 932 Nm (Ss@932nm)mentioning
confidence: 99%
“…Its core numerical aperture (NA, ~0.14) has been designed to match with the standard single-mode fiber (SMF), e.g., the Nufern 1060-xp and Corning HI 1060. Typically, NDF exhibits a strong emission at around 1060 nm, and thus the NDF cavity easily oscillates at 1060 nm rather than 900 nm [16,17]. The NDF used here has a W-type refractive index profile, and more detailed information can be found iXblue.…”
Section: The Swept Source At 932 Nm (Ss@932nm)mentioning
confidence: 99%
“…Recently, few techniques were utilized to generate ultrashort pulses below 1 μm: femtosecond Yb-doped fiber laser amplification with optical parametric oscillator [16], [17], nonlinear frequency shift in a high-nonlinearity fiber [18], [19], frequency doubling of the 1.8-1.9 μm ultrafast laser emission [20], fiber-optic Cherenkov radiation technique inside a short piece of photonic crystal fiber [21] and direct generation using the neodymium-doped fiber (Nd-fiber) quasi-three-level F3/2 -4 I9/2 transition [22]- [31]. The last one is preferred due to its robustness and simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, grating pair with adjacent collimators with limited aperture size was implemented, causing strong spectrum filtering at 1060 nm and forced the laser to work at ∼900 nm [24], [26]. Another approach to suppress the strong laser oscillation at ∼1064 nm is to insert into the cavity a short-pass dichroic mirror with high transmission at ∼900 nm and high reflectivity at ∼1064 nm [22], [23]. Rusu et al have utilized original semiconducting saturable absorber mirror (SESAM) including 20 pairs of AlAs -Al0.2Ga0.8As quarter-wave layers and forming a distributed Bragg reflector with 100-nm reflection bandwidth (860-960 nm) to suppress emission at 1064 nm [27].…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al [3] demonstrated a passively mode-locked neodymium-doped oscillator featuring a W-type fiber operating at 930 nm with a pulse energy of 2.2 nJ and a pulse duration of 126 fs. Gao et al [4] reported a core-pumped all-normal dispersion mode-locked Nd-doped fiber laser at 910 and 935 nm with a pulse energy of 1.3 nJ and a pulse duration of 198 fs. Recently, Chen et al [5] demonstrated 4.4-nJ 114-fs pulses at ~910 nm using an optimized Nd-doped fiber amplifier, as well as 17-nJ 220-fs pulses at 930 nm [6].…”
Section: Introductionmentioning
confidence: 99%